Children as citizens education for participation - edited by Cathie Holden (Philadelphia J. Kingsley, 1998)
The social, moral and cultural development of children is a central concern for all schools. This book, which draws on the voices of children and practising teachers, demonstrates how such development can be promoted through children's readiness to discuss, debate and actively participate as young citizens. The various contributors, from Britain, other European countries and Australia, show how teachers can, as part of this process, develop young people's understanding of social justice, global responsibility, human rights, and, particularly, the rights of the child. In addition, contributors offer a critical appraisal of citizenship education with regard to such issues as disability, economics, the environment, racism and power sharing in schools. The book is thus timely, supporting teachers in the education of children for life as responsible adults, with social skills and values appropriate for the twenty-first century.
Includes bibliographical references and index.
Keywords: Citizenship--Study and teaching (Elementary)--Europe.